2014
DOI: 10.1371/journal.pone.0088370
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Tolerance to Host Cactus Alkaloids in Drosophila koepferae and D. buzzatii

Abstract: The evolution of cactophily in the genus Drosophila was a major ecological transition involving over a hundred species in the Americas that acquired the capacity to cope with a variety of toxic metabolites evolved as feeding deterrents in Cactaceae. D. buzzatii and D. koepferae are sibling cactophilic species in the D. repleta group. The former is mainly associated with the relatively toxic-free habitat offered by prickly pears (Opuntia sulphurea) and the latter has evolved the ability to use columnar cacti of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 68 publications
(86 reference statements)
2
44
0
6
Order By: Relevance
“…D. buzzatii showed and interesting variation in the time of emergence from pupae between cactus hosts while D. koepferae tended to be more resilient (a pattern previously observed on other traits; Soto et al ., ; Soto et al ., ; Soto et al ., ). Previous observations could be considered in the context of the present results.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…D. buzzatii showed and interesting variation in the time of emergence from pupae between cactus hosts while D. koepferae tended to be more resilient (a pattern previously observed on other traits; Soto et al ., ; Soto et al ., ; Soto et al ., ). Previous observations could be considered in the context of the present results.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of natural populations in the field and under laboratory conditions have shown that D. buzzatii and D. koepferae differ in their preferences regarding oviposition sites (Soto et al ., ) and higher viabilities, faster developing times and increased mating success for both species were observed when they were reared in their respective primary hosts (Soto et al ., ; Hurtado et al ., ). Here we enlarged the list of traits in which host‐dependent phenotypic plasticity is displayed by D. buzzatii whereas D. koepferae showed a more canalized behavior as previously observed for viability, developmental time (Soto et al ., ,b, , ), starvation resistance, oviposition preference (Soto et al ., ), and genital morphology (Soto et al ., ). As a performance‐related trait, time of pupal emergence was positively correlated with developmental time and negatively correlated with adult wing size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this respect, hostvector and host-microbe chemical interactions in the arid regions of South America may be analogous to those taking place in the Sonoran desert. So far, alkaloids isolated from T. terscheckii were shown to differentially affect fitness related traits in D. buzzatii and D. koepferae (Corio et al, 2013;Padr o et al, submitted;Soto et al, 2014), and samples of T. terscheckii and O. sulphurea have been shown to differ in their relative concentrations of medium-chain fatty acids Padr o and Soto, 2013). These two types of compounds are known to shape patterns of host use by cactophilic Drosophila and yeasts in the Sonoran desert (Fogleman and Danielson, 2001;Fogleman and Heed, 1989), however, their impact in the structure of other similar systems has been seldom considered.…”
Section: Introductionmentioning
confidence: 99%